Evaluation of the operational performance of unconventional intersections with high traffic flow - Saavedra, Steve (2023)
Currently, one of the worrying problems in vehicular traffic is the large number of cars making left turns at intersections. This phenomenon has generated various challenges in terms of road safety, traffic fluidity and transportation efficiency. To face this situation, today, alternative and innovative solutions are being proposed through the design of unconventional intersections. One of these is the displaced left turn (DLT) intersection. However, given that intersections of this type are few in Peru, it is necessary to evaluate the operational performance of this type of intersections. Therefore, this study evaluates the operability of DLTs using a scenario comparison study based on selected performance measures. For this, the case of a conventional intersection in the city of Lima is evaluated, in which the DLT was implemented in two accesses that have a greater flow of vehicles. The evaluation indicates that the DLT intersection proposed in this study has a high potential to reduce vehicular delays but may increase the number of conflicts. The study concludes by stating that, although the design with DLT reduces vehicular delays by 31.25%, at the same time it has negative impacts by increasing the number of vehicular conflicts by 73.57%. As a recommendation, it is suggested that appropriate safety measures be adopted, which must be designed and put into practice in order to increase the operability of the intersection.